Web-Based Bank Loan Information System Design at The PT. BPRS HIK Parahyangan - Aldo Luhukay; Ratnanto Aditiarno; Candra Mecca Sufyana (Politeknik Piksi Ganesha Indonesia, 2023)
Loan information systems at banks have the goal of providing the best loan services to customers and being able to improve bank operations. This study aims to design and create a bank lending information system application with a case study at PT. BPRS HIK Parahyangan West Bandung Branch. The research method was conducted qualitatively by conducting interviews, observation, and literature study. The software development method used is the prototype. The design of a bank information system uses the Unified Modeling Language (UML) and is implemented with the programming language PHP and My SQL as a database. Application test with the black box. With this application as a means of processing banking data, it can run quickly and optimally.